The Role of Married Couples in Realizing the Vision of Brunei Darussalam - Natasha, Saizatul; Muda, Zulkifly (Isti`dal : Jurnal Studi Hukum Islam, 2024)
Brunei Darussalam, in its pursuit of the national vision of Melayu Islam Beraja (MIB), the Brunei Vision 2035, and the Sustainable Development Goals (SDGs), necessitates effective implementation supported by robust contributions from household couples. In this context, couples play a crucial role in maintaining family harmony and well-being. However, current realities indicate that not all couples fully embrace their responsibilities in fostering harmonious and enduring domestic relationships. The primary focus of this study is to enhance awareness and understanding among couples regarding their roles within marriage, employing a qualitative approach. This awareness and understanding are essential for ensuring the stability of families. The anticipated outcomes of this research include providing guidelines on the rights and responsibilities of both spouses in achieving the nation's aspirations and the government's objectives to establish Brunei Darussalam as a peaceful, prosperous, and exemplary nation.